(untitled) (PSIKOLOGI KONSELING, 2025)
This study aims to provide an in-depth description of the application of Cognitive Behavior Therapy (CBT) through cognitive restructuring techniques in supporting the improvement of self-confidence in a student who experienced bullying at school. The research employed a descriptive qualitative approach with a case study design involving a tenth-grade female student who had been repeatedly subjected to verbal bullying by her classmates. Such experiences had led to several psychological impacts, including low self-esteem, social anxiety, and withdrawal from peer interactions. Data were collected through observations, in-depth interviews, and sociometric assessments to obtain a comprehensive understanding of the student’s emotional condition and social relationships before and after the counseling intervention. The findings indicate that the cognitive restructuring process has the potential to help the student identify, examine, and challenge negative automatic thoughts that previously shaped her self-perception. With guidance from the counselor, the student gradually developed more realistic and adaptive self-evaluations. After several counseling sessions, indications of improvement were observed in the areas of self-confidence, emotional stability, social engagement, and learning motivation. Although these results are preliminary and cannot be generalized, they provide early evidence that cognitive restructuring can be a useful approach for school counselors in supporting students who have experienced bullying and in fostering a safer, more supportive, and psychologically responsive school environment.